Huwag kang matakot - Donato, Celina Marie Perez 1992- (2013)
"Huwag Kang Matakot is a short film about fear. It is about two characters, a girl and her mother, who both experience fear one night. The girl, while watching her favorite television show, accidentally eats grape seeds. Assuming that they will eventually grow into plants inside her stomach, she prepares for her "untimely death", which included wearing her favorite white dress and kissing the poster of her celebrity crush. The mother, on the other hand, panics when she encounters a group of suspicious-looking men on her way home. She turns out to be wrong about them, as they were merely walking home just like her. The two characters meet. The girl, who apparently fell asleep waiting for her death, was woken up by her mother arriving. With their fears now realized to be nothing but false threats, the film ends. The films is guided by Semiotics, which focuses on the so-called cinematic language; as well as the Fear Appeal Theory and Protection Motivation Theory, with both serving as models for the idealization of the central concept fear."